(untitled) (Journal of the College of Basic Education, 2025)
Modern Arabic poetry is considered the beacon of the language and the last remaining hope for reviving the Arabic language in the hearts of intellectuals. The hijab is undoubtedly one of the religious obligations for women, and it is a symbol of chastity, reverence, and honor to protect our women. There is no doubt that poets in the past did not deal with hijab poetry in abundance. Except in narrow fields such as spinning and description. However, it appeared in religious poetry, and it rarely appeared in the context of pride or advocacy, because the public environment was conservative with the hijab in general, and nothing was known about the condition of women except for chastity and adherence to the hijab. The mention of the hijab in poetry has been present since ancient times, but in the modern era it has become more apparent and clear. With the presence of contemporary calls for civilization and other modern calls, some women were affected by this matter and abandoned the hijab and the legitimate Arab dress. A new type of poetic poetry emerged on the scene, which is the poetry of calling for the hijab, and the poetry of pride in the hijab and chastity, in addition to the image of the hijab in poetry that has been present since ancient times. Thus, one of the literary themes of religious poetry, which is (the poetry of the hijab), emerged on the scene strongly between an explicit call to wear the hijab, and between a reminder of chastity and reverence and that it is a crown of dignity, and between calls to reject adornment